Compliance with the principle of equal finding the truth in criminal proceedings – "sine qua non" principle - Paraschiv, Carmen Silvia (International Journal of Legal and Social Order, 2023)
Criminal procedural law includes a series of fundamental and specific principles and strict rules according to which the judicial bodies have the obligation to find out the truth in the criminal process. Finding the truth is subject to the collection of evidence related to the facts and circumstances of the case, the suspect, the defendant, as well as the other parties and the injured person. In order to fulfill this principle, it is necessary to comply equally with other basic rules embodied in the presumption of innocence, the right to defense, respect for human dignity, in fact all the rules that govern the conduct of the criminal process. Searching, discovering and finding out the truth are, in essence, the elements of a knowledge process. We can conclude, therefore, that any criminal trial fundamentally represents an extensive process of knowledge.